Survey of Japanese physicians' attitudes towards the care of adult patients in persistent vegetative state. Issue 4 (1st August 1999) - Asai, A; Maekawa, M; Akiguchi, I; Fukui, T; Miura, Y; Tanabe, N; Fukuhara, S
Abstract : OBJECTIVES: Ethical issues have recently been raised regarding the appropriate care of patients in persistent vegetative state (PVS) in Japan. The purpose of our study is to study the attitudes and beliefs of Japanese physicians who have experience caring for patients in PVS. DESIGN AND SETTING: A postal questionnaire was sent to all 317 representative members of the Japan Society of Apoplexy working at university hospitals or designated teaching hospitals by the Ministry of Health and Welfare. The questionnaire asked subjects what they would recommend for three hypothetical vignettes that varied with respect to a PVS patient's previous wishes and the wishes of the family. RESULTS: The response rate was 65%. In the case of a PVS patient who had no previous expressed wishes and no family, 3% of the respondents would withdraw artificial nutrition and hydration (ANH) when the patient did not require any other life-sustaining treatments, 4% would discontinue ANH, and 30% would withhold antibiotics when the patient developed pneumonia. Significantly more respondents (17%) would withdraw ANH in the case of a PVS patient whose previous wishes and family agreed that all life support be discontinued. Most respondents thought that a patient's written advance directives would influence their decisions. Forty per cent of the respondents would want to have ANH stopped and 31% would not want antibiotics administered if they were in PVS. CONCLUSIONS: Japanese physicians tend not to withdraw ANH from PVS patients. Patients' written advance directives, however, would affect their decisions.